ANALISIS MANAJEMEN SISTEM PELAYANAN ADMINISTRASI DALAM PENERIMAAN PASIEN BPJS DI RUANG IGD RSUD NOONGAN TAHUN 2024 - Britney Saerang; Prycilia P. Mamuaja; Bertom Ch. Pajung (JURNAL ILMIAH KESEHATAN MANADO, 2025)
This study aims to analyze the management of the administrative service system in the reception of BPJS patients in the Emergency Room (IGD) of RSUD Noongan in 2024. This research uses qualitative methods with a descriptive approach, involving in-depth interviews with relevant officers, field observations, and document analysis. The research results show that: (1) The planning process has a clear workflow with shift- based task distribution; (2) Service organization follows the established SOP; (3) Implementation is supported by competent human resources, adequate facilities, and the use of technology; (4) Supervision is conducted periodically with coordination between the hospital and BPJS Tondano to address operational constraints; (5) Evaluation is conducted regularly to improve service quality. Service to BPJS and general patients is provided without distinction, following the same SOP. This research concludes that the administrative service management at RSUD Noongan has been running according to the established standards, although improvements are still needed in staff training, technology development, and more intensive supervision.